REACCIÓN DEL MERCADO DE ACCIONES ESPAÑOL ANTE LA CONCESIÓN POR PRIMERA VEZ DE UN RATING A UN EMISOR - Verona Martel, María Concepción (2007)
The current article assesses the reaction of the spanish stock market in the face of the announcements being accomplished by the rating S&P, Moody’s and IBCA agencies.The results evidence that spanish stock market has no reaction against a first time grant in a rating.